EDTA interference in electrochemiluminescence ACTH assay. (November 2016) - Toprak, Burak; Yalcin, Hulya; Arı, Elif; Colak, Ayfer
Background: As plasma is the recommended sample type for Roche adrenocorticotropic hormone (ACTH) assay, we evaluated the effect of EDTA concentration on Cobas ACTH assay. Methods: Samples containing twofold and fourfold higher concentrations of EDTA were prepared by adding plasma to empty K2EDTA tubes and by making under-filled EDTA tubes. All measurements were performed with four replicates. Results: Increased EDTA concentration resulted in a significant decrease in ACTH concentration. Fifty-per cent-filled EDTA tube showed 19% decrease in ACTH concentration and 25% filled EDTA tube showed 50% decrease in ACTH concentration. Conclusion: We recommend that inadequately filled EDTA specimens should be rejected when using Cobas ACTH assay.